Incubation in a Temperate Passerine: Do Environmental Conditions Affect Incubation Period Duration and Hatching Success? - Higgott, Caitlin G.; Evans, Karl L.; Hatchwell, Ben J. (Frontiers in Ecology and Evolution, 2020)
The timing of breeding often has a profound influence on the reproductive success of birds living in seasonal environments with rapidly changing nestling food availability. Timing is typically investigated with reference to lay dates, but it is the time of hatching that determines the ambient conditions and food availability that nestlings experience. Thus, in addition to lay date, phenological studies may also have to take account of variation in the length of the incubation period, which is likely to depend on both environmental conditions and parental traits. The primary aim of this study was to use a 24-year dataset to investigate the abiotic and biotic factors influencing variation in incubation duration in long-tailed tits (Aegithalos caudatus), a species in which incubation duration varies substantially (range: 12–26 days). We found support for our predictions that drier conditions, later breeding attempts and larger clutches were associated with shorter incubation periods. Larger clutches were also more resilient to increases in incubation duration associated with wet conditions. Surprisingly, warmer ambient conditions were associated with longer incubation periods. Secondly, we assessed the consequences of variation in the length of incubation periods for the risk of nest predation and the hatching success of surviving clutches. We show that longer incubation periods are likely to be costly due to increased exposure to nest predators. In contrast, we found only marginal effects of environmental conditions or incubation duration on hatching success, implying that wet conditions cause slower embryo growth and hence longer incubation periods, rather than causing embryo fatality. We suggest that long-tailed tits’ nests and parental behavior protect eggs from mortality arising directly from adverse weather conditions.